2021
DOI: 10.1098/rstb.2019.0739
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental stress on ageing in a termite species with low social complexity

Abstract: Social insects seem to have overcome the almost universal trade-off between fecundity and longevity as queens can be highly fecund and at the same time reach lifespans of decades. By contrast, their non-reproducing workers are often short-lived. One hypothesis to explain the long lifespan of queens is that they are better protected against stress than their workers. However, evidence is controversial and experimental studies are scarce. We aimed at manipulating environmental stress and ageing by exposing colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
1
22
1
Order By: Relevance
“…This may be in line with the idea that these workers do not work hard [63] and that workers are totipotent immatures in this species [64]. In fact, a study in which stress was introduced through temperature variation in C. secundus also showed that workers mounted their oxidative stress response by increasing the expression of antioxidant genes under stressful temperature conditions more than queens [65]. This was explained by the fact that, as wood-dwelling, one-piece nesters, C. secundus workers are totipotent immatures that are selected to invest in body maintenance as they have not reached maturity yet.…”
Section: (C) the Role Of Reproductionsupporting
confidence: 77%
See 1 more Smart Citation
“…This may be in line with the idea that these workers do not work hard [63] and that workers are totipotent immatures in this species [64]. In fact, a study in which stress was introduced through temperature variation in C. secundus also showed that workers mounted their oxidative stress response by increasing the expression of antioxidant genes under stressful temperature conditions more than queens [65]. This was explained by the fact that, as wood-dwelling, one-piece nesters, C. secundus workers are totipotent immatures that are selected to invest in body maintenance as they have not reached maturity yet.…”
Section: (C) the Role Of Reproductionsupporting
confidence: 77%
“…This again highlights the view that reproductive division of labour has strong effects on traits that are closely related to longevity. For C. secundus, the results of the temperature stress experiment imply that ROS defence mechanisms are similar across castes but that the castes experience oxidative stress differently [65].…”
Section: (C) the Role Of Reproductionmentioning
confidence: 99%
“…Like several of the former papers, this focuses on oxidative stress and identifies striking similarities, such as the role of peroxiredoxins, antioxidant enzymes, which in mammals appear to play a protective role in neurodegenerative disorders involving stress and seem to improve brain function in old honeybees. A role for peroxiredoxins also became evident in several other transcriptome studies in this volume [30,32,33]. Furthermore, Quigley & Amdam [49] also stress the importance of social interactions in modulating senescence in humans, similar to what has been shown in social insects and social rodents [33,40,43,46,47].…”
Section: Contributionsmentioning
confidence: 58%
“…Additionally, transcriptome analyses reveal a clear oxidative stress defence signal (including Prx3) under constant conditions, which is stronger in workers than queens. These at first sight unexpected results can be explained by the fact that workers of this species are totipotent immatures, which have not yet reached maturity [32].…”
Section: Contributionsmentioning
confidence: 93%
See 1 more Smart Citation